SHARIA HOUSING: MARKETING STRATEGY IN PROPERTY BUSINESS AT SUKAMANAH ISLAMIC VILLAGE PURWAKARTA - Muhammad Fauzan Nur Syaban; Ade Irvi Nurul Husna; Adriansah (Journal of Finance, Economics and Business, 2024)
The purpose of this research is to determine the marketing strategy implemented by Sharia Housing based on the theory explained by Philip Kotler and Gary Armstrong, namely market segmentation, market targeting, market positioning and differentiation. The research method used is descriptive qualitative. The research was conducted in one of the sharia housing complexes located in Purwakarta Regency, West Java Province. Data collection was carried out by observation, interviews and documentation studies. Researchers triangulated data sources. Researchers examine in depth programs, events, processes and activities related to the research object. The research results show that the market segments determined are divided into four segments, namely based on psychographic factors, potential consumers want housing with a sharia residential concept with usury-free financing; based on demographic factors, the average potential customer is 28-50 years old; based on geographical factors, prospective customers work as employees who work in the nearest industrial area; Based on behavior, prospective consumers on average work as employees. Housing managers set a target market, namely potential buyers who have incomes above 5 million rupiah. Differentiation and market positioning, housing which is the differentiator is the type of house. There is the American Farmhouse house type which has become a housing icon.